Earleria quadrata - Peter Schuchert; Aino Hosia; Lucas Leclère (Zenodo, 2017)
Earleria quadrata (Hosia & Pages, 2007) Figs 5-6 Foersteria quadrata Hosia & Pages, 2007: 180, fig. 5. in part Campanulina panicula G. O. Sars, 1874: 121, pl. 5 figs 9-13. ? Campanulina panicula . ‒ Kramp, 1941: 1, figs 1-5. – Cornelius, 1995: 190, fig. 43. – Schuchert, 2001: 56, fig. 41, Iceland. ? not Opercularella panicula . – Vervoort, 1966: 104, figs 4-5. – Vervoort, 1972: 40, fig. 11a, Nicaragua (Pacific), Peru. – Leloup, 1974: 4, fig. 3 ? Racemoramus panicula . – Calder, 2012: 26, fig. 24. not Campanulina panicula. – Schuchert, 2003: 150, fig. 10, Indonesia. Type locality: Korsfjorden, 25 km south of Bergen, Norway,> 500 m deep. References: For the medusa see Hosia & Pages (2007), for the hydroid see Cornelius (1995), Schuchert (2001), or Calder (2012). Published as part of Peter Schuchert, Aino Hosia & Lucas Leclère, 2017, Identification of the polyp stage of three leptomedusa species using DNA barcoding, pp. 167-182 in Revue suisse de Zoologie 124 (1) on page 177, DOI: 10.5281/zenodo.322675